The application of prospect theory in travel choice behavioral analysis - Hariharan Subramaniam. (2012)
The study of travel behaviour is increasingly recognised as an important concern for providers of transport services and researchers. It involves the process of decision making and choice behaviour which has a long tradition of application in various disciplines such as statistics, political sciences, economics and psychology. This study adopts the Prospect Theory as a framework of travel choice behavioural analysis.